Law No. 24 of the Year 2018 On Amending Some Provisions of Law No. 10 of the Year 1990 Concerning Expropriation of Real Estates for Public Benefit = قانون رقم 24 لسنة 2018 بتعديل بعض أحكام القانون رقم 10 لسنة 1990 بشأن نزع ملكية العقارات للمنفعة العامة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic